2012
DOI: 10.1016/j.rbmo.2012.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Soluble BAFF-R produced by decidual stromal cells plays an inhibitory role in monocytes and macrophages

Abstract: A sophisticated immunological regulation between decidual stromal cells (DSC) and monocytes and macrophages is essential for the successful symbiosis of the mother and her fetus, but the mechanisms remain incompletely understood. The mRNA and proteins of B lymphocyte stimulator (BAFF, also known as BLys) and its receptor, BAFF-R (also known as BR3, CD268 or TNFRSF17), have been detected in both first-trimester and term placentas, but whether BAFF or BAFF-R participates in the cross-talk between DSC and monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The same group showed that sBCMA can also be shed by plasmacytoid dendritic cells via a similar γ‐secretase‐dependent cleavage . One study has reported the existence of sBAFF‐R, a soluble form of the receptor released by human decidual stromal cells ex vivo , and an inhibitory role in the regulation of interleukin (IL)‐6 and TNF secretion by monocytes has been suggested . Some published studies have reported the presence of soluble forms of BAFF receptors in human serum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group showed that sBCMA can also be shed by plasmacytoid dendritic cells via a similar γ‐secretase‐dependent cleavage . One study has reported the existence of sBAFF‐R, a soluble form of the receptor released by human decidual stromal cells ex vivo , and an inhibitory role in the regulation of interleukin (IL)‐6 and TNF secretion by monocytes has been suggested . Some published studies have reported the presence of soluble forms of BAFF receptors in human serum.…”
Section: Introductionmentioning
confidence: 99%
“…9 One study has reported the existence of sBAFF-R, 10 a soluble form of the receptor released by human decidual stromal cells ex vivo, and an inhibitory role in the regulation of interleukin (IL)-6 and TNF secretion by monocytes has been suggested. 10 Some published studies have reported the presence of soluble forms of BAFF receptors in human serum. All three soluble BAFF receptors have been reported in rheumatoid arthritis, 11 and sTACI and sBCMA have been described in multiple sclerosis, multiple myeloma and patients with chronic lymphocytic leukaemia.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that the placenta secretes BAFF. Both in early and term pregnancies BAFF accompanied by its receptor could be detected in the placenta [45]. Trophoblasts and stromal cells of the decidua were shown to express BAFF.…”
Section: Discussionmentioning
confidence: 97%
“…Trophoblasts and stromal cells of the decidua were shown to express BAFF. Furthermore, BAFF-R secretion was suggested to be an inherent property of decidual stromal cells [45], and this soluble BAFF-R might inhibit the functions of macrophages. Therefore, the BAFF system might play a vital role in the successful pregnancies.…”
Section: Discussionmentioning
confidence: 99%